Pengaruh Penggunaan E-Money Dan QRIS Terhadap Kemudahan Bertransaksi Mahasiswa Pendidikan Ekonomi Angkatan 2021 Universitas Negeri Medan - Rowinna Siburian; Angela Anggraini; Putri Damayanti Saragih; Venus Situmeang; Hasyim Hasyim (Journal on Education, 2024)
This research aims to analyze the influence of E-Money and QRIS on the ease of transactions among economic education students class of 2021, Medan State University. The method used in this research is a quantitative approach with the analytical model used is multiple regression analysis, with data collected through questionnaires distributed to 41 respondents. The analysis results show that the calculated T value for E-Money is 2.503, exceeding the T Table of 1.683, and the T Calculated for QRIS reaches 5.941, also higher than the same T Table. In addition, the F Calculated value is 197.9004, much greater than the F Table of 2.86, indicating the overall significance of the model. The adjusted R-Squared reached 87.25%, indicating that E-Money and QRIS contributed significantly in explaining variations in ease of transactions. These findings underscore the importance of using both payment methods in increasing transaction efficiency among students. These results confirm that the use of E-Money and QRIS not only has a positive impact, but also has a significant relationship in increasing the ease of transactions. This means that both play an important role in facilitating the transaction process, which can improve the overall user experience.